The Role Of The School Principal In Improving The Performance Of Islamic Religious Education Teachers At SDN 17 Singkawang - Ihsyan Sutrisno; Purniadi Putra; Dewi Ferawati (CV PUTRA PUBLISHER, 2026)
This research is based on the phenomenon that improving the quality of education in Indonesia, particularly at SDN 17 Singkawang, requires an effective principal role in improving the performance of Islamic Religious Education (PAI) teachers. This research focuses on three main aspects of the principal's role in improving PAI teacher performance at SDN 17 Singkawang: (1) planning the principal's role in motivating PAI teachers, (2) implementing the principal's role in improving PAI teacher performance, and (3) evaluating the principal's role in improving PAI teacher performance. This research uses a qualitative approach with descriptive methods. Data collection techniques were conducted through observation, in-depth interviews, and documentation studies with the headteacher and PAI teachers at SDN 17 Singkawang as research subjects. The results show that 1) the headteacher's planning at SDN 17 Singkawang to motivate PAI teachers involves the preparation of a comprehensive School Work Plan (RKS), including professional development through training and teacher competency development. 2) In its implementation, the headteacher functions as a supervisor who provides guidance and constructive feedback to Islamic Religious Education teachers. 3) The evaluation conducted showed a significant increase in discipline, creativity, and student learning outcomes, which reflects the effectiveness of the headteacher's role in improving the performance of Islamic Religious Education teachers. The headteacher also actively provides motivation and rewards to teachers for their achievements, as well as developing a harmonious and collaborative working atmosphere among teachers and school staff.